Complete transection of third part of duodenum following blunt injury abdomen: a rare case report - Basheer, Noufal Thekkekara; Venkatesan, Jothiprasad; Pravallika, Amaradeepthi; Subramaniam, Sureeskumar; Sarveswaran, Venugopal (International Surgery Journal, 2020)
Blunt injury abdomen (BIA) is an ever-increasing problem. Isolated injury to duodenum following BIA is rare (1-4%). It can be a challenge to the surgeon and failure to manage it properly can lead on to devastating results. Blunt duodenal injury can occur in isolation or with pancreatic injury. We report a case of an isolated transection of third part of the duodenum following BIA. Initial clinical changes in isolated duodenal injury may be subtle before life-threatening peritonitis develops. High index of suspicion, knowledge of mechanism of injury, physical examination and proper imaging techniques are the key in early detection of duodenal injury.